Inflammatory Diseases of the Brain - Hh̃nel, Stefan. (Medical Radiology, 2013)
Inflammatory diseases of the CNS are playing an increasingly important role in the clinical practice of neuroradiology. Neuroimaging contributes greatly to the differentiation of infectious (e.g., viral encephalitis and pyogenic brain abscess) and noninfectious (e.g., multiple sclerosis) inflammatory brain diseases and to the distinction between brain inflammation and other brain diseases, e.g., neoplastic or ischemic. This second, updated edition of Inflammatory Diseases of the Brain provides a comprehensive overview of the field from a neuroradiological point of view. In order to ensure a standardized approach throughout the book, each disease-oriented chapter is again subdivided into three principal sections: epidemiology, clinical presentation, and therapy; imaging; and differential diagnosis. A separate chapter addresses technical and methodological issues and imaging protocols. An important focus of the book is the current role of advanced MR imaging techniques, such as diffusion and perfusion MRI and MR spectroscopy, in the differentiation of inflammatory and other brain diseases. All of the authors are recognized experts, and the numerous high-quality and informative illustrations include some not contained in the first edition. This book will be of great value not only to neuroradiologists but also to neurologists, neuropediatricians, and general radiologists.